The impact of job stress on job satisfaction among academics of public university in Selangor / Nur Shafini Mohd Said ... [et al.] - Mohd Said, Nur Shafini; Mazelan, Nurfarhana Iylia; Omar Ali, Siti Rapidah; Mat, Khalid Amin; Abdullah, Nasiha (Universiti Teknologi MARA, Kedah, 2021)
The study investigate s the impact of job stress satisfaction among academics of on job public university in Selangor. The purpose of the study is to analyze the relationships between the factors that affect stress, which are Workload, Role of Ambiguity and Role of Conflict. The researchers have selected the academicians from the public university in Selangor as the study population, which involved 320 academicians. The statistical analyses were performed using version 23 of the Statistical Package for Social Science (SPSS). In order to identify the impact of job stress on job satisfaction, the Correlation and Multiple Regressions analyses were used. The results s howed that there is a weak relationship between ind ependent and dependent variables. The researchers hope that the results will also provide numerous benefits to the organization.